MIRRORING SUSTAINABILITY: HARNESSING DIGITAL TWIN WORKSHOPS FOR OPTIMAL ENERGY EFFICIENCY - Wang, Xinyi (International Journal of Allied Sciences (IJAS), 2023)
In response to the latest wave of industrial innovation and the call for sustainable and green manufacturing, China introduced "Made in China 2025" in 2015, emphasizing innovation-driven development and quality enhancement. A key component of this initiative is the comprehensive promotion of green manufacturing projects. However, the traditional manufacturing sector faces challenges related to energy consumption and environmental impact, necessitating the adoption of modern production technologies for industry optimization and advancement. Notably, digital twin technology, initially employed for aerospace health maintenance in the United States, and the establishment of "Digital Twin Cities" in the UK for engineering solutions and low-carbon urban environments have demonstrated the transformative potential of this technology. China, in its "Fourteenth Five-Year Plan," has strategically harnessed digital twin technology to drive high-quality socio-economic development, presenting promising opportunities for technological innovation and emerging economic growth.